The Effect of Teacher Administration Arrangement and Information Systems in the Implementation of the Education Unit Curriculum (KSP) on the Quality of Madrasah Aliyah Education in Pandeglang Regency, Banten Province - Suwenti, Reni; Masdariah, Een; Kurniawati, Eti; Mujib, Abdul; Nugraha, Enung (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the influence of teacher administration arrangement and the application of information systems in the implementation of the Education Unit Curriculum (KSP) on the quality of education at Madrasah Aliyah, Pandeglang Regency, Banten Province. This study uses a quantitative descriptive approach with data collection through observations, questionnaires, and interviews with madrasah heads, supervisors, teachers, and the Curriculum Development Team. The data were analyzed using descriptive and inferential statistical techniques to uncover the relationship between the variables studied. The results of the study show that the arrangement of teacher administration and the use of information systems have a significant effect on the quality of education, by having an impact on increasing the effectiveness and efficiency of education management in madrasas. This research is expected to contribute to improving the quality of education in madrasas through administrative management.